2020
DOI: 10.1590/0034-7167-2019-0175
|View full text |Cite
|
Sign up to set email alerts
|

Older adults with physical disabilities: vulnerabilities relative to the body, the physical and social environment

Abstract: Objective: to understand the vulnerabilities of older adults with physical disabilities regarding their body, physical and social environments. Method: this was a qualitative study based on Alfred Schütz’ social phenomenology, with 15 older adults with physical disability from Cuiabá, state of Mato Grosso, Brazil. Open-ended questionnaires were administered to the participants in 2017. The units of meaning that emerged were organized into thematic categories. Results: physical decline, associated with the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Tais doenças ainda representam desafios globais para a saúde pública e podem resultar em muitas complicações graves se não forem adequadamente controladas, principalmente em grupos mais vulneráveis, o que pode contribuir para o surgimento de deficiências ou agravar as existentes, dificultando as atividades da vida diária (23) . As pessoas com deficiência apresentam maior suscetibilidade a comorbidades e, por conseguinte, maior probabilidade de desenvolverem deficiências adquiridas, o que explica o elevado índice de causas relacionadas a complicações de doenças (24)(25) .…”
Section: Discussionunclassified
“…Tais doenças ainda representam desafios globais para a saúde pública e podem resultar em muitas complicações graves se não forem adequadamente controladas, principalmente em grupos mais vulneráveis, o que pode contribuir para o surgimento de deficiências ou agravar as existentes, dificultando as atividades da vida diária (23) . As pessoas com deficiência apresentam maior suscetibilidade a comorbidades e, por conseguinte, maior probabilidade de desenvolverem deficiências adquiridas, o que explica o elevado índice de causas relacionadas a complicações de doenças (24)(25) .…”
Section: Discussionunclassified
“…13 Regarding the care of the elderly, there is a need for support in face of the impacts associated with environmental and social barriers, in addition to the vulnerabilities present in the aging process. 14 A study in Africa showed that the difficulties of access to health care in a rural area is greater for people with disabilities and has implications for older people facing the challenges of caring for this population. 15 As people age, the likelihood of becoming a caregiver for an elderly relatives increase considerably, however, studies with caregivers in the community are scarce, especially when they live in remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to possible limitations in relation to carrying out activities of daily living, elderly face several obstacles, including attitudinal, environmental, and institutional barriers, which prevent their full and equal participation in all aspects of life (Martins et al, 2020 ). When evaluating social participation, this study could observe an average score of 14.99 (74.9%) which demonstrates that there is a loss of social participation within this group, although it is still a regular average, since other studies suggest a significant loss in social participation of the elderly(O. Figueira et al, 2020 ), while reinforcing the importance of social interaction as a measure to promote QOL.…”
Section: Discussionmentioning
confidence: 99%